Teknik Budidaya Sayuran Secara Vertikultur Di Pekarangan Untuk Ketahanan Pangan Keluarga - Ir. Shodiq Eko Ariyanto, MP; Untung Sudjianto (Universitas Muria Kudus, 2022)
The purpose of community service is to optimize the use of the yard to support family food security, help fulfill the family's vegetable needs, and improve community nutrition with family food security. In general, the yard in Pati Kidul Village, Pati District, Pati Regency is still quite potential, so it is necessary to look for a vegetable cultivation technique in the yard to get satisfactory results. The method used is to provide provision in developing techniques for cultivating vegetables in the yard. In addition, training and technical assistance to cultivate vegetables in the yard in verticulture were also carried out to support family food security and. increase in community income. The results of this activity can increase knowledge about sixty percent compared to when they have not implemented technology transfer and direct practice. All participants showed adequate skills when practicing, starting from making planting media, planting, maintaining vegetable crops in their yards. The output of the activity was in the form of a vegetable cultivation technique model and publications in ISSN journals and national seminars.